2019
DOI: 10.1111/pcn.12850
|View full text |Cite
|
Sign up to set email alerts
|

Brain neurochemistry in unmedicated obsessive–compulsive disorder patients and effects of 12‐week escitalopram treatment: 1H‐magnetic resonance spectroscopy study

Abstract: Aim The purpose of this study was to examine treatment‐related neurochemical changes in 28 unmedicated obsessive–compulsive disorder (OCD) patients using 1H‐magnetic resonance spectroscopy (1H‐MRS). Methods We included subjects diagnosed with OCD (n = 28), each with a total duration of illness of less than 5 years, as a study group and age‐ and sex‐matched healthy controls (n = 26). The inclusion criteria for the OCD group were right‐handed individuals aged 18 years or older who had not been on any specific tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“… 33 Some recent studies on OCD have also found changes in the levels of inositol metabolism in the brain. Parmar et al 38 have found significant increase in inositol levels in the caudate nucleus and anterior cingulate cortex of OCD. It is positively correlated with the compulsive symptoms and disease severity, and it is speculated to be related to the potential reversible abnormalities in regulating the neuro-osmotic pressure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 33 Some recent studies on OCD have also found changes in the levels of inositol metabolism in the brain. Parmar et al 38 have found significant increase in inositol levels in the caudate nucleus and anterior cingulate cortex of OCD. It is positively correlated with the compulsive symptoms and disease severity, and it is speculated to be related to the potential reversible abnormalities in regulating the neuro-osmotic pressure.…”
Section: Discussionmentioning
confidence: 97%
“… 35 , 37 Additionally, a study with the effect of 12-week treatment using citalopram on NAA/Cr ratios in 13 drug-naive patients with OCD showed a significant increase in the bilateral prefrontal cortex, frontal white matter and anterior cingulate when compared to those before treatment. 38 So, the decrease of NAA/Cr ratios in the lPFC might indicate gray matter volume reduction and neuronal damage in OCD, which is closely related to verbal working memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In MRI, water molecules are detected to produce a spatial map of the brain, but for MRS the focus is on detecting metabolite signals in specific brain regions (typical voxel size: 4-8 cm 3 ) (170); these metabolites can be neurotransmitters like glutamate (171)(172)(173) or γ-aminobutyric acid (GABA) (174)(175)(176). The psychopharmacological approach to 1 H MRS involve studies that monitor neurotransmitter changes in response to anti-depressant medication (177)(178)(179), and similarly, this approach can be used to study psychedelics. In 2017, an open label uncontrolled 1 H MRS study was conducted to measure metabolite change in the brain 24 h after (post-acute) administration of ayahuasca (containing 0.64 mg/kg of DMT) in healthy volunteers (180).…”
Section: Future Directions For 1 H Nmr In Psychedelic Researchmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy ( 1 H‐MRS) is a non‐invasive technique which can explore brain metabolism in vivo. It is widely used to investigate various neuropsychiatric diseases such as brain tumors, obsessive‐compulsive disorder, Alzheimer's disease, and epilepsy 10,11 . It can be used to observe many metabolites in the brain, such as N‐acetyl aspartate (NAA), myo‐inositol (Ins), choline (Cho), creatine (Cr), and glutamate +glutamine (Glu + Gln, Glx).…”
Section: Introductionmentioning
confidence: 99%